2019
DOI: 10.1158/1078-0432.ccr-18-2740
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of the Indoleamine 2,3-Dioxygenase 1 (IDO1) Inhibitor Navoximod (GDC-0919) Administered with PD-L1 Inhibitor (Atezolizumab) in Advanced Solid Tumors

Abstract: Purpose: IDO1 induces immune suppression in T cells through L-tryptophan (Trp) depletion and kynurenine (Kyn) accumulation in the local tumor microenvironment, suppressing effector T cells and hyperactivating regulatory T cells (Treg). Navoximod is an investigational small-molecule inhibitor of IDO1. This phase I study evaluated safety, tolerability, pharmacokinetics, and pharmacodynamics of navoximod in combination with atezolizumab, a PD-L1 inhibitor, in patients with advanced cancer.Patients and Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
163
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(170 citation statements)
references
References 20 publications
5
163
1
1
Order By: Relevance
“…The findings of this study are in line with those of the firstin-human study of navoximod monotherapy [13], and the combination study of navoximod and atezolizumab [12]. In the monotherapy study, 22 patients with advanced or recurrent solid tumours received monotherapy with navoximod 100 mg, 200 mg, 400 mg, 600 mg or 800 mg twice daily for 21 days, followed by 7 days without treatment, or 600 mg twice daily continuously.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The findings of this study are in line with those of the firstin-human study of navoximod monotherapy [13], and the combination study of navoximod and atezolizumab [12]. In the monotherapy study, 22 patients with advanced or recurrent solid tumours received monotherapy with navoximod 100 mg, 200 mg, 400 mg, 600 mg or 800 mg twice daily for 21 days, followed by 7 days without treatment, or 600 mg twice daily continuously.…”
Section: Discussionsupporting
confidence: 83%
“…As a result, the recommended dose of navoximod monotherapy was determined as 1000 mg twice daily. In combination with atezolizumab, the recommended dose of navoximod could not been determined because of early discontinuation of enrollment based on limited evidence of clinical activity in the clinical study conducted for the same time [12]. However, even though navoximod 1000 mg twice daily in combination with atezolizumab was administered in one patient, there was no safety concern, as such the navoximod 1000 mg twice daily in combination with atezolizumab 1200 mg every 21 days could be considered as recommended dose in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In human patients, epacadostat monotherapy was not effective (163,164), while combined administration with PD-1 or cytotoxin T-lymphocyte-associated protein 4 (CTLA-4) inhibitors showed promising clinical activity in phase I/II studies (165)(166)(167)(168). Unfortunately, a recent trial with combined administration of epacadostat with pembrolizumab found no superiority over pembrolizumab alone (169).…”
Section: Immune Tolerance Related To Indoleamine 23-dioxygenase 1 Acmentioning
confidence: 99%
“…Single and twice daily oral doses (up to the maximum assessed dose of 1000 mg) of navoximod monotherapy are well tolerated in clinical studies in cancer patients; therefore, a single 200 mg oral dose was considered suitable for this study. A 5 mg intravenous (IV) dose was selected based on pharmacokinetic simulations, with a predicted C max below the median C max of a 200 mg oral dose (assuming a conservative absolute bioavailability of 0.5).…”
Section: Methodsmentioning
confidence: 99%
“…Clinically, navoximod has favourable safety, tolerability and pharmacokinetic profiles when given as a monotherapy or in combination with atezolizumab, a PD‐L1 inhibitor . Navoximod is rapidly absorbed and demonstrates linear pharmacokinetics with dose‐proportional increases in exposure over the dose range of 50–1000 mg. Navoximod has a half‐life of approximately 12 hours, supporting a twice daily (BID) dosing regimen.…”
Section: Introductionmentioning
confidence: 99%